Reduction Techniques of Peak-to-Average Power Ratio in MC-CDMA Systems - Mayada Faris Ghanim; M.F.L Abdullah (International Journal of Informatics and Communication Technology (IJ-ICT), 2012)
The high peak-to-average power ratio (PAPR) is one of the main disadvantages of multicarrier code division multiple access (MC-CDMA) system. To reduce the PAPR of multicarrier CDMA signals, a lot of studies have been focused on the power characteristics of spreading sequences. This paper presents the main techniques to reduce the PAPR in MC-CDMA like Amplitude Clipping and Filtering, Coding, Selective Mapping, The adaptive predistortion technique and DFT Spreading. Then a comparison of all these techniques is done in order to clarify the main advantages and disadvantages of each technique.DOI: http://dx.doi.org/10.11591/ij-ict.v1i2.558